Mid-to Late Holocene landscape reconstruction of the Maye Estuary (Picardy, Northern France) and its implications for human occupation. (10th November 2021) - Desruelles, Stéphane; Ghilardi, Matthieu; Cloquier, Christophe; Delanghe, Doriane; Buchot, Yannick; Hermitte, Daniel; Parisot, Jean-Claude; Hoeblich, Jean-Marc
Abstract: The town of Rue was one of the most important coastal harbours of Picardy, Northern France, from the beginning of the 12th century to the end of the 15th century CE. Document sources and ancient maps confirm the existence of this vibrant harbour. Until now, however, no palaeoenvironmental studies have attempted to reconstruct the configuration of the region's coastline during medieval times. Here we employ a geoarchaeological approach to reconstruct the Mid-to Late Holocene shoreline and landscape changes in the Rue area. Our approach includes a geophysical survey (Electric Resistivity Tomography method) and a series of eight sediment cores that reveal the region's chronostratigraphy. Document sources were also used to shed light on the landscape configuration during the Late Middle Ages (ca. 1300 CE). Our coring results, based on sedimentological analyses, are combined with 2D geophysical profiles down to 21.50 m. This reveals, firstly, that a calm marine environment prevailed at the beginning of the 4th millennium BCE, particularly in depressions bordered by Pleistocene coastal spits ( foraines ). Secondly, from ca. 3500 BCE to ca. 1000 BCE, coastal swamps predominated. Then, thirdly, at around 1000–1250 CE, an estuarine depositional environment prevailed, prior to a final period of land reclamation of the former Maye Estuary from the 13th century CE onwards. These results agree well with recent work on sea level changes along the Atlantic and English Channel coasts of France, where continuous post-glacial sea level rise has been observed. Our study also proposes a location of the medieval harbour of Rue to the west of the town at the upstream boundary of the upper part of the Maye Estuary, near ' Le Moulin de Saint-Jean', although archaeological evidence of the exact site of this tidal harbour is still lacking.